Methods to overcome of the dormancy in murici (Byrsonima verbascifolia Rich) seeds - Paula Sperotto Alberto (Semina: Ciências Agrárias, 2011)
The great agricultural development in the Brazilian savannah brought with it the reduction of its natural vegetation, which has been quickly lost, especially due to extractive exploitation by man. Murici (Byrsonima verbascifolia Rich) is a fruit bearing plant of great medicinal importance in the savannah; however, its propagation is hindered by the fact that the seeds have low germination and seedling emergence in the field is slow. This study evaluated the effect of different dormancy breakage methods in murici seeds. Therefore, were evaluated effect of different temperatures; soaking in gibberellic acid and water; chemical and mechanical scarification and two types of substrate (distilled water and KNO3). Treatments were arranged in a randomized block design. Records made daily on the number of germinated seeds were used to determine the germination percentage and germination speed index. Among the methods evaluated, giberellic acid at 2,309.46 μM gave the greatest seed germination percentage, especially when the germination paper was moistened with KNO3.